2016
DOI: 10.1016/j.respol.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of interpartner dissimilarities in Industry-University alliances: Insights from a comparative case study

Abstract: Based on a comparative study of two alliances, this paper provides an in-depth examination of the role of interpartner dissimilarities in Industry-University (IU) alliances. We make a conceptual distinction between routine-based dissimilarities (differences in partners' behavior) and orientation-based dissimilarities (differences in partners' goals and expectations), illuminating their joint implications for collaborative processes and outcomes over time. Our findings reveal that interpartner dissimilarities m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 54 publications
2
71
0
2
Order By: Relevance
“…This means that while firms are likely to choose topics and problems that are valuable for the development of new products and services for customers, universities are likely to choose research topics that are perceived as interesting and valuable by peers (Nelson, ). In addition, recent research has suggested that firms and universities (or government‐funded institutions in general) are dissimilar in both their orientation and in their routines (Estrada, Faems, Cruz, and Santana, ), and that, relative to firms, universities' knowledge is often more tacit, and therefore more difficult for firms to learn and to make use of (Kodama, Yusuf, and Nabeshima, ). Overall, these differences indicate that the problems that private and public partners may explore in research are very different and the kinds of knowledge outputs each type of partners is interested in diverge (Bruneel, D'este, and Salter, ).…”
Section: Hypothesesmentioning
confidence: 99%
“…This means that while firms are likely to choose topics and problems that are valuable for the development of new products and services for customers, universities are likely to choose research topics that are perceived as interesting and valuable by peers (Nelson, ). In addition, recent research has suggested that firms and universities (or government‐funded institutions in general) are dissimilar in both their orientation and in their routines (Estrada, Faems, Cruz, and Santana, ), and that, relative to firms, universities' knowledge is often more tacit, and therefore more difficult for firms to learn and to make use of (Kodama, Yusuf, and Nabeshima, ). Overall, these differences indicate that the problems that private and public partners may explore in research are very different and the kinds of knowledge outputs each type of partners is interested in diverge (Bruneel, D'este, and Salter, ).…”
Section: Hypothesesmentioning
confidence: 99%
“…It is important to understand where firms focus most of their managerial attention as it can influence how decisions and actions are taken and prioritised in organisations (Ocasio, ). Existing literature on alliances argues that cross‐partner differences in orientation, involving perception of the purpose and objectives of the alliance, are harder to overcome compared to routine‐level dissimilarities, with findings suggesting that placing attention to the latter leads to neglecting the former due to trade‐offs and eventually to alliance failure (Estrada et al, ). Research on alliances and informal external knowledge sourcing also identifies trade‐offs in managerial attention, arguing that when firms form formal relationships they divert their attention towards their management and tend to benefit less or none at all from informal knowledge spillovers arising from co‐location (Fernhaber and Li, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As cross‐partner knowledge proximity eases knowledge sharing and internalisation it is expected that in intra‐industry alliances there is recognition and understanding of cross‐partner idiosyncrasies allowing for increased awareness of the requirements for effective interaction (Cohen and Levinthal, ; Lane and Lubatkin, ; Estrada et al, ). As a result, intra‐industry alliances, reduce complexity and ambiguity (Rothaermel and Deeds, ) and require relatively low managerial attention (Ocasio, ; Estrada et al, ), allowing firms to retain focus. This may induce firms to dedicate their scarce managerial resources to more challenging tasks (Penrose, ).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple data sources were used for that purpose, including in‐depth interviews with general directors and technological transfer coordinators from the four centers ( n = 11), who provided a more inward comprehension of their organizational management mechanisms. To mitigate potential retrospective bias in data collection, the results of the interviews were cross‐referenced with information in official documents (Estrada, Faems, Martin Cruz, & Perez Santana, ). The 57 examined documents included biannual and annual TC reports, as well as CONACYT annual reports, both types of documents from between 2010 and 2014.…”
Section: Method: Study Field Case Selection Research Design Informmentioning
confidence: 99%